Optimization of the Production Process using the Theory of Constraints (TOC) Method based on Drum-Buffer-Rope (DBR) Improvements - Destiara Nabila Widyarsa; Rr. Rochmoeljati (Sistemasi: Jurnal Sistem Informasi)
One footwear manufacturing company located in Surabaya has experienced an increase in production demand for both women's and men's sandals in recent years. The main issue faced by the company is the presence of bottlenecks at specific workstations due to unbalanced capacity, which disrupts the smooth flow of the production process. To address this issue, the study applies the Theory of Constraints (TOC) method based on the Drum-Buffer-Rope (DBR) concept, in combination with Linear Programming (LP). The research stages include identifying the constraints, exploiting the constraints, subordinating non-constraints, and elevating the constraints. The analysis results indicate that the coating and bonding workstations are the main constraints affecting the system's throughput. To overcome this, overtime was added at these workstations to increase production capacity. The implementation results showed an improvement in throughput from IDR 39,849,260 with 1,594 units to IDR 46,490,330 with 1,860 units, reflecting a 14.3% increase. These findings demonstrate that the application of TOC and DBR can effectively balance the production flow, optimize bottleneck workstations, and enhance overall production throughput.